Sex Differences of Human Cardiac Progenitor Cells in the Biological Response to TNF-α Treatment - Elisabetta Straface; Lucrezia Gambardella; Francesca Pagano; Francesco Angelini; Barbara Ascione; Rosa Vona; Elena De Falco; Elena Cavarretta; Raffaele La Russa; Walter Malorni; Giacomo Frati; Isotta Chimenti (Hindawi Limited, 2017)
Adult cardiac progenitor cells (CPCs), isolated as cardiosphere-derived cells (CDCs), represent promising candidates for cardiac regenerative therapy. CDCs can be expanded in vitro manyfolds without losing their differentiation potential, reaching numbers that are appropriate for clinical applications. Since mechanisms of successful CDC survival and engraftment in the damaged myocardium are still critical and unresolved issues, we aimed at deciphering possible key factors capable of bolstering CDC function. In particular, the response and the phenotype of CDCs exposed to low concentrations of the multifunctional cytokine tumor necrosis factor α (TNF-α), known to be capable of activating cell survival pathways, have been investigated. Furthermore, differential biological responses of CDCs from male and female donors, in terms of cell cycle progression and cell spreading, have also been assessed. The results obtained indicate that (i) the intracellular signaling activated in our experimental conditions is most likely due to the prosurvival and proliferative signaling of TNF-α receptor 2 and that (ii) cells from female patients appear more responsive to TNF-α treatment in terms of cell cycle progression and migration ability. In conclusion, the present report highlights the hypothesis that TNF-stimulated CDCs isolated from females may represent a promising candidate for cardiac regenerative therapy applications.